Clinical Features of Patients with Exfoliation Glaucoma Requiring Surgical Intervention. (19th June 2020) - Nakano, Hideyuki; Togano, Tetsuya; Sakaue, Yuta; Suetaka, Aki; Iikawa, Ryu; Nakano, Rieko; Fukuchi, Takeo
Abstract : Purpose . To clarify the clinical features of patients with exfoliation glaucoma (XFG) requiring surgical intervention. Study Design . Retrospective study. Methods . The study included 46 eyes from 36 XFG patients, 85 eyes from 53 primary open-angle glaucoma (POAG) patients, and 54 eyes from 35 normal-tension glaucoma (NTG) patients. Age, duration of previous glaucoma treatment, intraocular pressure, medication scores, visual function, and surgical procedure were compared among the three patient groups. Results . The XFG group had the highest mean age (XFG: 75.7 ± 8.3 years, POAG: 65.8 ± 12.8 years, and NTG: 53.3 ± 12.8 years; p < 0.001 ) and the shortest mean duration of previous treatment with glaucoma medication (XFG: 5.1 ± 3.5 years, POAG: 8.9 ± 6.9 years, and NTG: 8.9 ± 5.9 years; p < 0.001 ). Intraocular pressure and medication scores were slightly higher in the XFG group than in the POAG group, although the differences were not significant. Among XFG patients, trabeculectomy was performed in 20 eyes from 16 patients (55.6%) and trabeculotomy was performed in 16 eyes from 14 patients (44.4%). Both trabeculectomy (3 eyes) and trabeculotomy (14 eyes) were performed in combination with cataract surgery. Conclusions . The XFG patients referred to our department for initial examination were older than the POAG and NTG patients, and their duration of treatment before referral was shorter. Moreover, intraocular pressure and the eye drop medication score were higher in the XFG patients. A significantly higher percentage of XFG patients required surgical intervention compared to patients with other disease types.